Вплив лазерної енергії на властивості наночастинок оксиду галію для покриття поверхні сонячних панелей - Marwa , K.A.; Ali , H.A.; Farah, S.A.; Haitham, T.H. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2026)
In order to develop coatings to optimize the functioning of the solar panels, this study examines how laser energy affects the morphology, size, and optical properties of gallium oxide (Ga2O3) nanoparticles prepared through the use of pulsed laser deposition. The precursor powder is pressed into small particles, which are referred to as Ga2O3 pellets, and the thin films are deposited on the glass substrates prepared with extreme care onto the glass surface using Nd : YAG laser pulses. The nanoparticles preferred crystallographic orientation and phase composition is determined by using X-ray diffraction analysis. Ultraviolet visible spectroscopy is then applied to determine their transmittance, absorbance and optical band-gap. Fringes of optical interference are measured to arrive at the thicknesses of the films and a double-beam spectrophotometer gives the correct values of the optical constants. The topography is analyzed using atomic force microscopy and more specific height maps are created to assess the dispersion and homogeneity of grains - between which is vital in the obtaining of a homogenous light absorption and low scale of reflectance. It is observed in the experimental findings that a strong preferential orientation exists along the (111) plane, and that there are monoclinic crystal structures which develop in the films. The intensity of diffraction peaks is enhanced by increasing the energy of deposition. At the same time, a growth in the thickness of the film increases internal forces and simultaneously decreases the size of crystallites. High transmittance and low absorption in the ultraviolet region are indicated by optical measurements, and the band-gap is becoming narrower with thickness, with direct-band-gap semiconductor behaviour. In general, the research provides an explanation of the morphology, structure, and optical characteristics of the Ga2O3 nanoparticles, which are essential materials to understand how to create the best possible coating on solar panels in order to improve their energy-converting efficiency and service life.